The Role Of Social Environment On The Development Of Pre-School Age Children (3-5 Years) In Dharma Wanita Tosaren Ii Kindergarten School Kediri City - Intan Fazrin; Sri Anggun M Radjak (Journal of Global Research in Public Health, 2023)
A negative social environment can cause the delayed process of giving stimulation, especially cognitive stimulation to children. The aim of this study was to determine the relationship between the role of social environment and development of pre-school children (3-5 years) at Dharma Wanita Tosaren II Kindergarten, Kediri City. This study used correlational analytic design with cross sectional approach. Respondents were taken by accidental sampling technique. There were 35 children as the sample. The independent variable is the role of social environment and the dependent variable is development of pre-school children (3-5 years). Researcher analyzed the result with spearman rank statistical test. The results showed that the role of social environment were 29 (83%) in a good category. In addition, the development of pre-school children (3-5 years) were 32 (91%) in the appropriate category. The significance level was 0.000 < = 0.05 means that H0 was rejected and H1 is accepted. It was concluded that there was a strong relationship in the role of social environment and development of pre-school children (3-5 years). Teachers and parents were recommended to provide a good stimulation, facilitate and give a positive to children so that they are able to improve their abilities well.